2018
DOI: 10.1093/hcr/hqy004
|View full text |Cite
|
Sign up to set email alerts
|

When Visual Cues Activate Moral Foundations: Unintended Effects of Visual Portrayals of Vaping within Electronic Cigarette Video Advertisements

Abstract: Within multimodal persuasive messages, the roles of visual cues in producing unintended effects have been understudied. In an experiment on a sample of former and current smokers (N = 991), we manipulated the presence of visual vaping cues within electronic cigarette video advertisements (N = 25) to evaluate opinions towards vape-free policies. Such cues diminished the effects of pro-vaping arguments to increase support for vape-free policies, inadvertently benefiting public health. Consistent with the moral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
3
10
0
Order By: Relevance
“…Although vaping is not completely safe, former smokers are better off if they develop positive intention to vape rather than consider smoking. However, if they start and continue vaping over a long period, then they might relapse though some evidence suggest that this might not happen Consistent with prior research (Yang et al 2018), results from waves one and two surveys also revealed that awareness of e-cigarette advertising in retail outlets significantly predicted never smokers' cognitive attitudes, which in turn affected intention to vape. The results are worrying because never smokers who develop stronger cognitive attitudes towards vaping perhaps because of greater exposure to e-cigarette advertising might decide to start vaping and consider experimenting cigarette smoking and become long-term daily cigarette smokers.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Although vaping is not completely safe, former smokers are better off if they develop positive intention to vape rather than consider smoking. However, if they start and continue vaping over a long period, then they might relapse though some evidence suggest that this might not happen Consistent with prior research (Yang et al 2018), results from waves one and two surveys also revealed that awareness of e-cigarette advertising in retail outlets significantly predicted never smokers' cognitive attitudes, which in turn affected intention to vape. The results are worrying because never smokers who develop stronger cognitive attitudes towards vaping perhaps because of greater exposure to e-cigarette advertising might decide to start vaping and consider experimenting cigarette smoking and become long-term daily cigarette smokers.…”
Section: Discussionsupporting
confidence: 74%
“…Once cognitive responses of potential users (e.g., former smokers) are triggered, this may reflect favourable or unfavourable evaluations of the attitude object, i.e. the stimulus (Fishbein & Ajzen 1975;Yang et al 2018). In this regard, marketing messages that promote the health benefits of e-cigarettes may create favourable cognitive responses among consumers (Rüther et al 2015).…”
Section: Cognitive and Affective Responses To Advertising Messagementioning
confidence: 99%
See 3 more Smart Citations